Unraveling Second Language Acquisition Hurdles: A Qualitative Exploration Among University Students in Rawalpindi and Islamabad - Raina Tabbasum (University of Chitral Journal of Linguistics and Literature, 2024)
Language learning is a multifaceted process that implies a range of internal and external learner-based dimensions. Although numerous empirical studies have been conducted to acquire knowledge on second language acquisition, one of the neglected areas involves the identification of socio-cultural barriers in Pakistani people. The current research proposal was intended to fill this gap by conducting a qualitative study analyzing the issues of second language learners in Rawalpindi and Islamabad. In the present investigation, we analyze the hurdles university students in Rawalpindi and Islamabad encounter while attempting to acquire Second language acquisition, especially in the English language. To get a better depiction of the situation, we have compiled information through structured interviews with university students of BS. Students face certain problems like pronunciation, a lack of motivation, and resources that may hinder the process of learning English. Furthermore, the influence of students’ mother tongue on their English acquisition is quite significant. In addition, we analyzed several teaching methods used in the literature as well as their impact. However, motivation also significantly affects the result, so we explore the relationship between motivation to acquire English and students’ progress. Fortunately, there is also some good news. Moreover, we found efficient ways that might help students tackle these problems including peer practice and using multimedia. In conclusion, our study suggests that it might be difficult for university students in Rawalpindi and Islamabad to become proficient in English. However, with the proper support and methods, students can undoubtedly improve their English abilities.